Sea-level exercise performance following adaptation to hypoxia: A meta-analysis - Bonetti, D. L.; Hopkins, W. G. (Sports Medicine, 2009)
Adaptation to living or training in hypoxic environments (altitude training) continues to gain interest from sport scientists and endurance athletes. Here we present the first meta-analytic review of the effects on performance and related physiological measures following adaptation to six protocols of natural or artificial hypoxia: live-high train-high (LHTH), live-high train-low (LHTL), artificial LHTL with daily exposure to long (8-18 hours) continuous, brief (1.5-5 hours) continuous or brief (<1.5 hours) intermittent periods of hypoxia, and artificial live-low train-high (LLTH).